Positive Factors of Student Learning Orientation in Improving Student Understanding and Learning Outcomes - Wijayanto, Pikir Wisnu; Suarni, Ertati; Judijanto, Loso; Putri Zalika LM Kesuma; Huda, Nuril (International Journal of Elementary Education, 2024)
The low results of learning mathematics from year to year give rise to students' perception that mathematics is a difficult subject. This needs to be researched to analyze the relationship between mathematics learning attitudes, anxiety, and habits, and evaluate additional mathematics learning outcomes. Quantitative research method with a survey approach. The research subjects were 253 people using random sampling. The data collection technique uses an instrument adapted from Learning Orientation which includes attitudes, attention, and study habits totaling 52 items. The analysis technique uses correlation and regression with SPSS version 26.0 software. The research results show that attitudes, habits, and anxiety are positively and significantly related to learning. Learning anxiety has a moderate relationship, while attitudes and study habits have a weak relationship with increasing learning achievement. Another finding is that learning anxiety is the main predictor of additional material, compared to attitudes and study habits. In conclusion, learning orientation is one of the factors that plays a very important role in determining the level of student learning achievement. This contribution provides information that students who have a positive attitude in learning show good study habits, therefore the teacher's role is needed to build a positive attitude.